Penerimaan Keluarga dengan Interaksi Sosial pada Orang dengan HIV - Dwiyanti Purbasari; Ahmad Syaripudin (Jurnal Keperawatan Silampari, 2022)
This study aims to identify the relationship between family acceptance and social interaction in people with HIV. This research method uses descriptive correlation research through a cross-sectional approach. The results of the univariate analysis showed that there were 39 respondents (81.3%) in the excellent family acceptance category and 26 respondents (52.4%) in the high social interaction category for people with HIV, and the Spearman rank test found a positive and moderate correlation between family acceptance and social interactions in people with HIV (p=0.000; <Î±=0.05, r = 0.522). In conclusion, families and patients treat HIV-infected family members through acceptance and favorable treatment to help overcome external or internal pressure and prevent HIV education for families with sufferers. Keywords: HIV, Social Interaction, Family Acceptance